2015
DOI: 10.25242/885x5112015602
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Da Água De Abastecimento Da Comunidade Tamarindo Em Campos Dos Goytacazes/Rj

Abstract: Considerando que a água é um elemento essencial para a vida e que a qualidade da água fornecida à população tem influência direta em sua saúde, este estudo tem o objetivo de verificar a qualidade da água de abastecimento da Comunidade Tamarindo, localizada na cidade de Campos dos Goytacazes/RJ.  As comunidades são caracterizadas pela ocupação irregular e de baixa renda, cuja população representa uma parcela da sociedade excluída da maioria dos serviços públicos que deveriam ser prestados a todos os cidadãos. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…In a study conducted in favelas, it was observed that 58.8% of tap water samples, which were not in accordance with the Brazilian Regulation, obtained positive results for total coliforms and positive for E. coli (Pereira et al, 2015). According to De Souza et al (2015), slums in the city of Campos dos Goytacazes, Rio de Janeiro, presented a sample of tap water at home outside the established bacteriological standards for water quality, with a level 35 times higher of UFC/ml of total coliforms above the permitted by law and 10 times the UFC/ml level of thermotolerant coliforms above that allowed by regulation. The presence of coliforms in the water indicates the possible presence of other pathogenic microorganisms and their absence indicates that other organisms are not present in the water (Sotero-Martins et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in favelas, it was observed that 58.8% of tap water samples, which were not in accordance with the Brazilian Regulation, obtained positive results for total coliforms and positive for E. coli (Pereira et al, 2015). According to De Souza et al (2015), slums in the city of Campos dos Goytacazes, Rio de Janeiro, presented a sample of tap water at home outside the established bacteriological standards for water quality, with a level 35 times higher of UFC/ml of total coliforms above the permitted by law and 10 times the UFC/ml level of thermotolerant coliforms above that allowed by regulation. The presence of coliforms in the water indicates the possible presence of other pathogenic microorganisms and their absence indicates that other organisms are not present in the water (Sotero-Martins et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Other Brazilian slums also do not have regular water supply even located in the urban area of the city, as in the case of the Tamarindo slum. This slum has clandestine pipes to obtain water (De Souza et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A preocupação com o meio ambiente e os impactos ambientais está dando espaço ao surgimento de um novo tipo de consumidor: o consumidor verde. Segundo Souza et al (2015), os consumidores verdes são aqueles que demonstram sua preocupação pelo meio ambiente através do seu comportamento na hora da compra, buscando produtos que preservem a integridade do meio ambiente.…”
Section: Conscientização Ambientalunclassified
“…O sabor produzido pelo íon cloreto em água potável varia de acordo com a sua concentração e também em função da composição química da água. Assim, a água com concentração de 250 mg/l pode apresentar um sabor salino perceptível, quando o cátion presente na solução for o sódio (Na + ) ( De Souza et al, 2015).…”
Section: Análises Físico-químicasunclassified